Penguatan Identitas Kebangsaan Anak PMI di Malaysia Melalui Konsep Bhinneka Tunggal Ika - Siagian, Nur Abni Rahmadani; Nursafirayanti, Tazkia; Bellapadma, Ayasha Jevon Azarlia; Law, Eni; Rahmawati, Syifa Nadia; Talita, Nailyssa; Pangaribawa, Fadli Delian; Putri, Ni Putu Keisha Adinda Wira; Ashfiya, Sayida Nur; Azizah, Siti Nur (Prioritas: Jurnal Pengabdian Kepada Masyarakat, 2024)
Some children of Indonesian Migrant Workers (PMI) in Malaysia are classified as stateless children. This condition triggers an identity crisis caused by their lack of knowledge about culture and other aspects of Indonesia. Limited access to formal education makes it difficult for them to learn more about the culture and history of their nation. To be able to survive in Malaysia, which is classified as a multicultural country, PMI children need to be equipped with social skills through a teaching project program. The method used was the delivery of material about Bhinneka Tunggal Ika and Indonesia's diversity, as well as interactive sessions that included ice breaking and games. Learning about Bhinneka Tunggal Ika and Indonesia's diversity is given to PMI Malaysian children aimed at strengthening their national identity and increasing their spirit of nationalism. There are several challenges during the learning process, starting from children's difficulty in focusing and concentrating to limited delivery time. The visible impact after implementing this program is increasing knowledge about Bhinneka Tunggal Ika and diverse Indonesian culture.